Waiting for Goldie - Gates, Susan (Oxford Oxford University Press, 2014)
In Waiting for Goldie Danny's grandad is in hospital, so Danny must record the time that Grandad's champion racing pigeon, Goldie, returns from the race. What will Danny do when Goldie doesn't come back? TreeTops Fiction contains engaging novels from top authors and illustrators with the variety children need to develop a love of reading!
Include Illustrations
Keywords: Racing pigeons -- Grandfathers -- Welsh language